2009
DOI: 10.1080/09286580902863007
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Prevalence of Self-Reported Visual Impairment in Older Adults Among U.S. Race-Ethnic Subgroups

Abstract: Purpose Prevalence of visual impairment (VI) in the United States (US) has not been carefully examined by race-ethnic subgroups. This study examines self-reported VI prevalence in race-ethnic subgroups using data representative of the US population age ≥45 years. Methods The National Health Interview Survey (NHIS) is a population-based multipurpose and multistage area probability annual survey of the US civilian non-institutionalized population conducted by the National Center for Health Statistics. Data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…For example, in a longitudinal study of adults in England, Matthews and colleagues (12) reported that worsening self-reported vision predicted decreases in social engagement and well-being, though they did not test the mediating pathways between these variables. The few studies that have explored the mediating effect of social activity on the association between VI and well-being have focused on social support rather than social participation, and results have been mixed (19,37). The current study contributes to this debate by demonstrating that self-reported VI was significantly and independently associated with participation restrictions, but that this did not mediate the association between VI and SWB.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…For example, in a longitudinal study of adults in England, Matthews and colleagues (12) reported that worsening self-reported vision predicted decreases in social engagement and well-being, though they did not test the mediating pathways between these variables. The few studies that have explored the mediating effect of social activity on the association between VI and well-being have focused on social support rather than social participation, and results have been mixed (19,37). The current study contributes to this debate by demonstrating that self-reported VI was significantly and independently associated with participation restrictions, but that this did not mediate the association between VI and SWB.…”
Section: Discussionmentioning
confidence: 47%
“…There may have also been selection bias, wherein sicker respondents were more likely to be lost to follow-up or die, which could have biased results toward the null hypothesis since they may have been at greater risk for poor vision, activity limitations, and SWB decline (3). Though self-reported vision status has been widely used in prior population-based studies (37,38), there could be a confounding effect of personality type. Future work should corroborate this study's findings using objective measures of visual function like visual acuity and contrast sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…NHATS relies on self‐report, which can be subject to recall bias. Although self‐reported vision is not perfectly correlated with visual acuity, self‐reported vision has been widely used in prior population‐based studies, and previous studies have found that the 2 measures may have a strong positive association . NHATS respondents were also asked to recall falls from the prior year, but the validity of the NHATS falls questions has not been tested against prospective falls diaries, which are known to be more accurate and are considered the criterion standard for falls reporting .…”
Section: Discussionmentioning
confidence: 99%
“…2007); however, other studies from the USA (Glynn et al. 1991, Lam et al. 2009), and a study from Finland (Koski et al.…”
Section: Introductionmentioning
confidence: 97%